Origin of pancreatic ductal adenocarcinoma from atypical flat lesions: a comparative study in transgenic mice and human tissues - Aichler, Michaela; Seiler, Christopher (The journal of pathology, 2011)
Pancreatic ductal adenocarcinoma (PDAC) and its precursor lesions, pancreatic intraepithelial neoplasia (PanIN), display a ductal phenotype. However, there is evidence in genetically defined mouse models for PDAC harbouring a mutated kras under the control of a pancreas-specific promoter that ductal cancer might arise in the centroacinar-acinar region, possibly through a process of acinar-ductal metaplasia (ADM). In order to further elucidate this model of PDAC development, an extensive expression analysis and molecular characterization of the putative and already established (PanIN) precursor lesions were performed in the Kras(G12D/+) ; Ptf1a-Cre(ex1/+) mouse model and in human tissues, focusing on lineage markers, developmental pathways, cell cycle regulators, apomucins, and stromal activation markers. The results of this study show that areas of ADM are very frequent in the murine and human pancreas and represent regions of increased proliferation of cells with precursor potential. Moreover, atypical flat lesions originating in areas of ADM are the most probable precursors of PDAC in the Kras(G12D/+); Ptf1a-Cre(ex1/+) mice and similar lesions were also found in the pancreas of three patients with a strong family history of PDAC. In conclusion, PDAC development in Kras(G12D/+); Ptf1a-Cre(ex1/+) mice starts from ADM and a similar process might also take place in patients with a strong family history of PDAC.
Gesehen am 04.04.2018